Verfahrensdokumente aus Kartellverwaltungsverfahren im Kartellschadenersatzprozess Die Wettbewerbsbehörde als Schaltstelle zwischen wirksamem Rechtsschutz und wirksamer Rechtsdurchsetzung - Freund, Benedikt (Münchener Schriften zum Europäischen und Internationalen Kartellrecht, 2022)
The thesis examines possible access routes to documents of the European Commission and the Swiss Competition Commission. At the heart of the thesis lies the question of whether the design and handling by the authorities of the access routes is in line with the aim of actions seeking compensation for cartel damages. To this end, the aim of these actions is explored and different access routes are examined. Finally, the access routes are analysed in regard to which extent the aim of these actions is actually met. The results then form subject of a legislative proposal that takes into account the aim of actions for cartel damages as well as the need for an effective public enforcement.